Can Japan enhance its 2030 greenhouse gas emission reduction targets? Assessment of economic and energy-related assumptions in Japan's NDC. (July 2019) - Kuriyama, Akihisa; Tamura, Kentaro; Kuramochi, Takeshi
Abstract: This study investigates the stringency of Japan's greenhouse gas emissions reduction target for 2030 (nationally determined contribution: NDC), focusing on the macroeconomic assumptions of Kaya indicators and others previously overlooked, e.g. GDP per working-age population. It also conducts a decomposition analysis in light of historic political and economic events. We find that the real GDP growth assumption underlying the NDC target is unrealistic. Namely, the real GDP per working-age population, which is an indicator of productivity, needs to be improved annually by 2.5% on average for 15 years, a high level that has not been observed since the collapse of the economic bubble in the early 1990s. Based on these findings and the data from mitigation scenarios, we conclude that Japan can achieve the NDC target (26% below 2013 levels by 2030) with existing mitigation measures and by resuming operations only at those nuclear power plants that come under the conformity assessment, assuming realistic GDP assumptions. If the government enhances mitigation measures promoting low-carbon technologies that are politically affordable in terms of costs with realistic GDP assumptions, then it would be possible to achieve 27–42% of GHG emissions reduction compared to the 2013 level, including the "no nuclear" scenarios. Highlights: Japan's NDC was assessed by the Kaya indicators and GDP-per working-age population. The GDP assumption of the NDC is optimistic. The assumptions of energy and carbon intensities in the NDC are achievable. Japan can enhance its GHG emissions reduction target with a modified GDP assumption.